Perceptions on osteoporosis of women at mid-life / Nur Ayuni Ahmad - Ahmad, Nur Ayuni (2014)
Background: Osteoporosis is a growing public health concern associated with rapidly increasing age. With rising life expectancy trends, Malaysia is projected to face increasing number of elder population which in tum may increase the risk of developing osteoporosis. Women at mid-life aged 40 to 55 years old are one of the groups that are most likely to get osteoporosis. While osteoporosis was shown to be an important factor associated with morbidity and mortality, it is important that the public understand and are aware of these issues. Objective: The aim of this study was to explore the perception and knowledge of osteoporosis for women at mid-life. Method: This was qualitative study. Participants were among women at mid life aged of 40 to 55 years with mix races working in Universiti Teknologi MARA (UiTM), Puncak Alam. All recorded interviews were transcribed in the form of script by listening to the recording while checking with the notes taken during the interviews. The data of the interviews were analyzed thoroughly several times. Thematic analysis was conducted to identify themes emerging from the interview scripts. Result: None of the subjects mentioned osteoporosis as a major health concern compared to other chronic conditions such' as heart disease and diabetes. Most of them were not aware about osteoporosis and also practicing poor preventive measures among the participants.